A major plant practice at Kanegie Food Km. 9 Barrio Pampanga, Sasa, Davao City - Oguis, Krisan Adilan (2006)
As part of University?s continuing effort to train students fro challenges in the food industry, the curriculum offered by the College of Science and Mathematics for the BS Food Technology (BSFT) program gives its students an option to choose between undergraduate thesis and practicum. The author opted for practicum and conducted her plant practice at Karnegie Food, Km. 9, Barrio Pampanga, Sasa, Davao City from April 18 ? May 25, 2006. The student was required to undergo 288 hours of practical training in a processing plant that manufactures pre-mix of Philippine delicacies and liquid food flavorings. She was allowed to directly participate in the actual plant operations. Problems were also encountered and recommendations were raised. In summary, it was a very satisfactory learning experience for the student to face the challenges of the food industry